2013
DOI: 10.1002/dc.22995
|View full text |Cite
|
Sign up to set email alerts
|

Subtyping of nonsmall cell lung cancer on cytology specimens: Reproducibility of cytopathologic diagnoses on sparse material

Abstract: Cytologic examination of fine-needle aspiration (material is increasingly used in diagnosing lung cancer. High interobserver agreement in distinguishing small-cell lung cancer from nonsmall-cell lung cancer (NSCLC) on cytologic material has been demonstrated. Because of new treatment-modalities, subclassification of NSCLC into squamous cell carcinoma (SQC) and non-SQC has clinical impact. Subclassification based on morphology alone may be difficult, but applying immunohistochemistry (IHC) to clot-material has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The accuracy of such subtyping in cytologic material is not well established, 11 particularly in reference to newer IHC stains such as p40, TTF-1, and napsin A. A few studies are available in the literature, 4,1015 but most are reports from single institutions with relatively small numbers of cases. One large series of 1182 transbronchial and transthoracic aspirates demonstrated that the positive predictive value of FNA in subtyping NSCLC was 92% for ADC and 82% for SqCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The accuracy of such subtyping in cytologic material is not well established, 11 particularly in reference to newer IHC stains such as p40, TTF-1, and napsin A. A few studies are available in the literature, 4,1015 but most are reports from single institutions with relatively small numbers of cases. One large series of 1182 transbronchial and transthoracic aspirates demonstrated that the positive predictive value of FNA in subtyping NSCLC was 92% for ADC and 82% for SqCC.…”
Section: Discussionmentioning
confidence: 99%
“…The greatest accuracy was achieved after the introduction of targeted therapy and with the use of IHC stains, 4,10,1315 suggesting that the criteria necessary to separate ADC from SqCC may not have been carefully applied prior to the recognition of the increased need for subtyping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the recognition of squamous cell carcinoma (SCC) is important because if this subset of lung carcinoma patients is given bevacizumab, then it may lead to serious pulmonary bleeding. [2]…”
Section: Introductionmentioning
confidence: 99%
“…[234] It is well documented that cytomorphology and immunohistochemistry (IHC) are useful in further categorization of NSCLC. [5] In centers where IHC is not readily accessible, a limited panel of antibodies can be used to categorize the tumor.…”
Section: Introductionmentioning
confidence: 99%